Social Commerce and Consumer Intention to Purchase (Evidence from Popular Social Networks in Iran) - Rahimi, Hamed (International Research Journal of Management, IT & Social Sciences, 2015)
The aim of this study is to investigate the relationship of consumer behavior in s-commerce by proposing a research model that incorporates various factors. To conclude, perceived usefulness and perceived enjoyment have a positive relationship on attitude. The proposed model that examines the mediating effects of attitude on variables. It is reported that perceived usefulness could be mediated by the effect of attitude, however perceived enjoy fullness doesnât not. As with any study of this nature, a number of limitations have to be pointed out. The first limitation is the issue of generalization. Small sample size collected in this study lead to the poor-fit structural model. Thus, the findings must be interpreted with caution and cannot be conclusively used to generalize to all the consumer behavior towards s-commerce. The second limitation relates to the cross-sectional nature of the current study.